2016
DOI: 10.1212/wnl.0000000000002238
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular thalamus

Abstract: Our data indicate that there are 2 anatomically distinct graviceptive signal processing mechanisms within the vestibular network in humans that lead, when damaged, to a vestibular tone imbalance either to the contraversive or to the ipsiversive side.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 39 publications
2
20
0
Order By: Relevance
“…However, a case report showed that thalamic astasia and SVV tilt also occurred in a patient with paramedian/centromedian thalamic stroke [57]. This was confirmed by a recent voxel-based behavioral mapping analysis that attributed SVV tilts to lacunar strokes of both posterolateral and central paramedian thalamic subnuclei [24]. Here two distinct systems of graviceptive processing within the thalamus were described: contraversive tilts of SVV were associated with lesions of the central and posterolateral nuclei, whereas ipsiversive SVV tilts were associated with regions located more inferior, involving nuclei endymalis thalami and inferior parts of the nuclei parafascicularis thalami.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…However, a case report showed that thalamic astasia and SVV tilt also occurred in a patient with paramedian/centromedian thalamic stroke [57]. This was confirmed by a recent voxel-based behavioral mapping analysis that attributed SVV tilts to lacunar strokes of both posterolateral and central paramedian thalamic subnuclei [24]. Here two distinct systems of graviceptive processing within the thalamus were described: contraversive tilts of SVV were associated with lesions of the central and posterolateral nuclei, whereas ipsiversive SVV tilts were associated with regions located more inferior, involving nuclei endymalis thalami and inferior parts of the nuclei parafascicularis thalami.…”
Section: Discussionmentioning
confidence: 77%
“…Of the latter, two patients showed ipsiversive tilts of the SVV; here the infarction partly affected inferior thalamic nuclei such as the nuclei endymalis thalami or parafascicularis thalami. These inferior parts of the thalamus convey parts of the vestibular graviceptive pathways [24]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding is important as it suggests that, in addition to involving the TPJ, the electrical stimulation “activates” a network of brain regions accounting for the complex phenomenal experience of OBEs. Both the TPJ and posterolateral thalamus have been involved in the sense of self-orientation and uprightness (Kheradmand et al, 2015 ; Baier et al, 2016 ; Kirsch et al, 2017 ) and the medial occipital cortex has been involved in autoscopic hallucinations (Jonas et al, 2014 ). A PET study during OBEs evoked by cortical electrical stimulation revealed activation beyond the TPJ, in the precuneus and the posterior thalamus (De Ridder et al, 2007 ).…”
mentioning
confidence: 99%